Pengaruh Kompetensi Karyawan dan Teknologi Informasi pada Kualitas Laporan Keuangan LPD Dengan Pendidikan Sebagai Pemoderasi - Pradnya Paramitha, A.A. Sg. Istri; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 26 No 1 (2019)DO - 10.24843/EJA.2019.v26.i01.p25, 2019)
This study aims to determine the effect of employee competence and information technology on the quality of LPD financial reports with education as a moderator. The data analysis technique used is MRA with Absolute Difference Test. The results of this study indicate that employee competence and information technology have a positive effect on the quality of financial statements. Education is not able to moderate the influence of employee competence on the quality of financial statements, but is able to moderate and strengthen the influence of information technology on the quality of financial statements. The results of this study are expected to be able to provide additional information to the parties - parties directly related to preparing financial statements to carry out their duties properly so that they will be able to produce quality financial reports. Keywords: financial report quality, employee competency, information technology, and education